Indian police : a study in fundamentals - Gautam, D. N. (New Delhi, 1993)
The book identifies basic issues, ideas and concepts to which various questions relating to Police-functioning can be. retraced. The book highlights ideological conradictions under which the Indian Police has to operate with its colonial origin in a new democratic setup, in absence of a national police policy.
Keywords: Police - India